1978
DOI: 10.2307/1540785
|View full text |Cite
|
Sign up to set email alerts
|

BIOLUMINESCENCE AND OTHER RESPONSES SPREAD BY EPITHELIAL CONDUCTION IN THE SIPHONOPHOREHIPPOPODIUS

Abstract: Conducting epithelia are known to play an important part in the behavior of several groups of animals including hydrozoan coelenterates and amphibian larvae (reviewed by Mackie, 1970;Spencer, 1974), and skin conduction has recently been reported in pelagic tunicates and ascidian tadpoles (Bone and Mackie, 1975;Mackie and Bone, 1976).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…In self-luminescent metazoans characterised by differentiated photogenic structures, emission is controlled either by hormones (Claes and Mallefet, 2009) or via coupling mechanisms between photocytes and excitable cells, including neural, muscular or epithelial cells (Herring and Morin, 1978;Anctil, 1987;Hastings and Morin, 1991;Krönström et al, 2009). Although luminescence can originate in a nerve-free bioluminescent epithelium, such as in the conducting epithelia of some Hydrozoa (Bassot et al, 1978;Dunlap et al, 1987) and Anthozoa (Germain and Anctil, 1996), it is most frequently controlled by neural pathways (Nicol, 1960;Case and Strause, 1978). In addition to turning the light emission on and off, nervous control abilities can modulate and adjust the intensity, duration, frequency or angular distribution of a light signal and thus generate diversity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…In self-luminescent metazoans characterised by differentiated photogenic structures, emission is controlled either by hormones (Claes and Mallefet, 2009) or via coupling mechanisms between photocytes and excitable cells, including neural, muscular or epithelial cells (Herring and Morin, 1978;Anctil, 1987;Hastings and Morin, 1991;Krönström et al, 2009). Although luminescence can originate in a nerve-free bioluminescent epithelium, such as in the conducting epithelia of some Hydrozoa (Bassot et al, 1978;Dunlap et al, 1987) and Anthozoa (Germain and Anctil, 1996), it is most frequently controlled by neural pathways (Nicol, 1960;Case and Strause, 1978). In addition to turning the light emission on and off, nervous control abilities can modulate and adjust the intensity, duration, frequency or angular distribution of a light signal and thus generate diversity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Within the cell, the bioluminescent system is further localized in granules with a pseudo crystalline structure, the photosomes (Pavans de Ceccaty er al., 1972, 1977Bassot, 1966a), which are part of, or concentrated in, the endoplasmic reticulum, and may be a local specialization of the endoplasmic reticulum. Image intensifier techniques have shown that these granules are indeed the source of light (Bassot and Bilbaut, 1977b). They are also fluorescent ; in vim these fluorescent particles correspond to the light emitting sources.…”
Section: Annelids: Acholiiementioning
confidence: 99%
“…Light emission moves from the centre of the scale to the exterior (Bassot and Bilbaut, 1977a), but at the intracellular level, light from granules moves from the exterior to the interior of the cell. This migration of activity can also be followed by fluorescence techniques (Bassot and Bilbaut, 1977b). A pace-maker type of autostimulation mechanism is present in the scale.…”
Section: Annelids: Acholiiementioning
confidence: 99%
“…But how related are the elements of these systems? Neuroid or non-nervous conduction in giant plant or algal cells such as Mimosa or Nitella (Fromm and Lautner, 2007) functions similarly to the neuroid conducting tissues of glass sponge syncytia, and to the gap junction-coupled epithelia of cnidarians, ctenophores and other animals (Mackie, 1965;Bassot et al, 1978;Hernandez-Nicaise et al, 1980;Leys and Mackie, 1997). Different ions form the basis of the action potentials (chloride and calcium potentials in the plant and alga, calcium in the sponge, and sodium or calcium in cnidarians and ctenophores) but the effect is similargenerating a rapid signal that effects a behavioural response.…”
Section: Introductionmentioning
confidence: 99%